Assessment of Cytokine Release against Oral Mucosal Cell Line Culture (TR146) Stimulated by Neutrophil Elastase Associated with Behcet’s Disease - Azeem Hussain Soomro; Erum Khan; Shafaq Noori; Mohid Abrar Lone; Zahid Syal; Sabir Sheikh (International Journal of Dentistry)
Aim. Cytokines and chemokines may be involved in the onset of oral ulcer in Behcet’s disease. The aim of our study is to assess the cytotoxic effects of proinflammatory cytokines and chemokines on reconstructed oral mucosal cell line (TR146) when treated with different concentrations of neutrophil elastase (NE). Objective. For this purpose, a culture of the oral mucosal model (OMM) prepared from a cell line derived from an oral squamous cell carcinoma of buccal mucosa (TR146) is treated with different concentrations of neutrophil elastase. The cultures were incubated for 4- and 24-hour intervals and designed as follows: culture + artificial saliva served as the negative control; culture + 0.01% SLS (sodium lauryl sulphate) served as the positive control; and culture + NE (10, 50, 100, and 200 nM) served as the treated group. Materials and Methods. We used sandwich ELISA technique to isolate IL-1β (interleukin 1β), IL-8, and TNF-α (tumor necrosis factor). Results. We found no significant level of IL-8 and TNF-α when treated with different concentrations of neutrophil elastase after 4- and 24-hour incubation. The IL-1β level was slightly higher when treated with 100 and 200 nM NE after 24 hours of incubation although a significantly high level was observed at 100 nM NE after 4 hours of incubation. Hence, we found an increase in the level of IL-1β when stimulating the reconstructed oral mucosal model (OMM) with different concentrations of NE. This is a preliminary in vitro study; however, further research is required to evaluate the cytotoxic effects of cytokines and chemokines released when treated with NE. Moreover, high concentrations of NE are recommended to stimulate the release of cytokines and chemokines against the OMM.